2021
DOI: 10.1016/j.ijid.2021.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Side effects and perceptions following Sinopharm COVID-19 vaccination

Abstract: Objectives : Vaccines are one of the best interventions developed for eradicating COVID-19,. The aim of this study to provide evidence on Sinopharm COVID-19 vaccine side effects. Methods : A cross-sectional survey study was conducted between January and April 2021 to collect data on the effects of COVID-19 vaccine among individuals in the UAE. Demographic data. vaccination, and the response of people not willing to take COVID-19 vaccine were reported. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
167
8
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(214 citation statements)
references
References 29 publications
34
167
8
5
Order By: Relevance
“…Comparable common side effects were reported during clinical trials in China [10,11]. Side effects after the Sinopharm vaccine, from clinical trials and real-world practice, were comparable to that of other vaccines [12,13]. Common side effects reported from Saudi Arabia, due to Pfizer -BioNTech COVID-19 vaccines, were in line with what was mentioned above.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Comparable common side effects were reported during clinical trials in China [10,11]. Side effects after the Sinopharm vaccine, from clinical trials and real-world practice, were comparable to that of other vaccines [12,13]. Common side effects reported from Saudi Arabia, due to Pfizer -BioNTech COVID-19 vaccines, were in line with what was mentioned above.…”
Section: Introductionsupporting
confidence: 78%
“…Comparably, Baden et al observed that the side effects after the Moderna vaccine were more frequent in the 18 to <65 years old group than the ≥65 years old group [24]. In real-world practice, the Sinopharm vaccine showed side effects that were more frequent in ≤ 49-year-old [13]. Generally, side effects represent a major determinant of vaccination acceptance.…”
Section: Introductionmentioning
confidence: 96%
“…Animal experiments and phase 1 and 2 clinical trials have consistently demonstrated that inactivated SARS-CoV-2 vaccines had notable immunogenicity and a low rate of adverse reactions [9]. A recent cross-sectional study showed side effects of the Sinopharm COVID-19 vaccination for the first and second doses were mild and predictable, and there were no hospitalization cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is little published data to corroborate adverse responses to the COVID-19 vaccination. Only a few studies discuss the side effects of the Sinopharm vaccines [15,18,[23][24][25]. The most common adverse effects of Sinopharm vaccination, according to these studies, were weariness, injection site pain, headache, fever, lethargy, chills, and myalgia.…”
Section: Introductionmentioning
confidence: 99%